Preparation method and application of boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst
By introducing Co and B elements into carbon-based catalysts, a highly graphitized, endogenous calcium-rich catalyst is constructed, which solves the problems of low antibiotic removal efficiency and risk of metal ion leaching in the prior art, and achieves efficient antibiotic removal within a wide pH range, which is stable and environmentally friendly.
Patent Information
- Application Number
- CN202411881516.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-19
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to efficiently remove antibiotics in water bodies, especially in a wide pH range, and traditional catalysts have problems with metal ion leaching risks and low electron transfer rates.
By introducing Co and B elements, a highly graphitized, endogenous calcium-rich carbon-based catalyst is constructed, combined with persulfate system, and synergistically with excellent adsorption and degradation, promoting the valence cycle of Co2+/Co3+, accelerating electron transfer, and realizing non-radical pathway-dominated antibiotic removal.
It achieves efficient removal of antibiotics within a wide pH range (3 to 11), avoids metal ion leaching problems, has high conductivity and reversible redox reactions, and has strong stability and universality.
Smart Images

Figure CN119701957A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a preparation method and application of a boron-cobalt coordinated graphitization calcium-rich carbon-based catalyst, belonging to the technical field of environmental catalysis and advanced oxidation. Background Art
[0002] With the extensive use of antibiotics in animal husbandry, pharmaceutical industry, etc., the content of antibiotics in water bodies has gradually increased. Once antibiotics enter the water environment, they cannot be completely removed by natural forces, and the sewage treatment plant has limited ability to handle antibiotics, resulting in a large amount of antibiotics remaining in the water. This will not only threaten the survival of aquatic plants and animals and make bacteria resistant, but it may also return to the human body through the flow of material and energy in various systems, turning medicine into poison and endangering human health.
[0003] Permonosulfate (PMS) oxidation is an efficient and stable organic matter treatment technology in advanced oxidation technology. Biochar, as a low-cost material, can help PMS to realize its value and has attracted widespread attention in the field of catalysis. However, biochar needs to be modified to maximize its resource utilization. Among them, doping with transition metals with high oxidation activity is efficient, but the risk of metal leaching and the electron transfer rate must be considered. Therefore, it is crucial to find a good carrier or construct an inclusive structure. In addition to the encapsulation effect of biochar itself, it is also necessary to regulate its pore characteristics, graphitization or its degree of defects. In the process of removing organic matter, compared with free radicals with higher redox potentials, non-free radicals will preferentially react with pollutants with electron donor groups, thereby improving the degradation efficiency of target pollutants and having anti-interference ability to complex water matrices. Generally, catalysts with a high degree of graphitization can not only accelerate electron transfer, but also promote the formation of non-free radicals. Therefore, it is of great significance to make transition metals participate in the construction of catalyst structure to make it easy to enter and difficult to exit, and accelerate the valence cycle of metals. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a boron-cobalt synergistic graphitization calcium-rich carbon-based catalyst with rich active sites, high degree of graphitization, no metal ion leaching, wide applicable pH range, fast electron transfer, anti-interference, and efficient activation of PMS, as well as a preparation method and application thereof.
[0005] The present invention introduces Co and B elements to construct a highly graphitized, endogenous calcium-rich, uniformly porous carbon-based low-cost catalyst, couples the persulfate system, synergizes the excellent adsorption and degradation effects, and improves the electrochemical performance of the catalyst by Co and B, and promotes Co through reversible redox reactions. 2+ / Co 3+ valence cycle, accelerate the electron transfer between substances, and promote O 2 ·- and1 O 2 The generation of electron-rich antibiotics in water bodies is achieved by non-radical pathways as the main method. In the production and preparation process of boron-cobalt synergistic graphitized calcium-rich carbon-based catalysts, the raw material cost is low, the operation is simple, and the energy consumption is low; the present invention avoids the problem of metal leaching in metal-doped catalysts during design, and the specific method is as follows: while incorporating the Co element, the material structure is optimized by the B element, and the Co and B elements regulate the endogenous Ca substances, so that Co and the carbon substrate are more closely combined. The obtained catalyst contains a small amount of Co but can exert a great catalytic effect, which is efficient and environmentally friendly; and Co compounds can broaden the pH application range, and the obtained catalyst is not limited to a narrow pH range in terms of application. It can also react efficiently under extreme pH conditions, and has strong stability and universality. The mechanism of antibiotic degradation by boron-cobalt synergistic graphitized calcium-rich carbon-based catalysts is mainly based on non-radical pathways.
[0006] The present invention provides a method for preparing a boron-cobalt coordinated graphitization calcium-rich carbon-based catalyst, using bamboo powder as a main raw material, and comprising the following steps: (1) mixing bamboo powder, boric acid, cobalt salt and water in a mass ratio of 5:0.5-1.5:0.1-1:50-100, and using a magnetic stirrer to achieve full impregnation; (2) placing the modified biomass obtained in step (1) into a tubular furnace, pyrolyzing it at 400-600° C. in a nitrogen atmosphere, washing, drying, and grinding to obtain a boron-cobalt doped boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst.
[0007] In the above preparation method, preferably, the cobalt salt in step (1) is cobalt nitrate hexahydrate, the magnetic stirring speed is 200 to 400 rpm, and the immersion time is 5 to 7 hours.
[0008] In the above preparation method, preferably, the pyrolysis time in step (2) is 1 to 3 hours, and the carbon source and calcium source of the catalyst are bamboo powder.
[0009] The present invention provides an application of a boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst in treating antibiotic wastewater. The catalyst and PMS are added to the polluted water simultaneously to achieve efficient removal of antibiotics. In addition, the catalyst can achieve 100% degradation of quinolone antibiotics such as ofloxacin and ciprofloxacin in about 30 minutes. The operation is simple and no special equipment is required.
[0010] Compared with the prior art, the invention is innovative in that it provides a method for preparing a boron-cobalt coordinated graphitization calcium-rich carbon-based catalyst. The main raw material of the catalyst is discarded bamboo powder, which is large in quantity and low in cost. Bamboo powder contains rich lignin, cellulose, calcium, magnesium, etc., and is an ideal carbon source for graphitized structure. When it is impregnated and modified with boric acid and cobalt salt, the relatively small atomic radius of boron makes it easy to enter the carbon lattice to replace sp2 and sp3 structures. Boron doping can not only increase the degree of graphitization of the material, but also promote Co 2+ / Co 3+ The circulation can also optimize the pore structure of the catalyst, increase the specific surface area, and increase the active sites. In addition, boron doping can also polarize the carbon surface, thereby promoting the electrostatic and ion-π interactions between the material surface and the solution ions. Co has a higher oxidation activity than other transition metals, which can not only promote the improvement of conductivity, but also broaden the pH application range of the catalyst. The boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst prepared from bamboo powder has a uniform porous structure, which not only increases the specific surface area, which is beneficial to the adsorption of oxidants and pollutants by the catalyst, but also provides abundant active sites and a stable loading environment.
[0011] Beneficial effects of the present invention: (1) In view of the problems of complex preparation and cumbersome process of existing catalysts, the present invention adopts a simple impregnation and pyrolysis method to achieve co-doping of heteroatoms and transition metals, and the raw material cost and equipment energy consumption are both economical; (2) The present invention uses boron and cobalt to prepare a biochar catalyst with a high degree of graphitization. 1 O 2 The generation of and acceleration of electron transfer enhance the non-radical pathway of pollutant removal, and achieve the selective removal of electron-rich organic matter; the mechanism of antibiotic degradation by boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst is mainly based on the non-radical pathway; (3) The boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst in the present invention can achieve efficient removal of antibiotics in a wide pH range (3 to 11); (4) The boron-cobalt-coordinated graphitized calcium-rich carbon-based catalyst of the present invention has high electrical conductivity, small resistance value, and a reversible redox reaction (Co 2+ / Co 3+ valence cycle).
[0012] (5) The boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst prepared by the present invention does not leach metal ions during the application process of treating antibiotic wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0013] Figure 1This is a SEM image of the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1 of the present invention.
[0014] Figure 2 XRD patterns of the original bamboo powder biochar (BC) prepared in Comparative Example 1 of the present invention, the boron-doped bamboo powder biochar (B-BC) prepared in Comparative Example 2, the cobalt-doped bamboo powder biochar (Co-BC) prepared in Comparative Example 3, and the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1.
[0015] Figure 3 The Raman spectra of the original bamboo powder biochar (BC) prepared in Comparative Example 1 of the present invention, the boron-doped bamboo powder biochar (B-BC) prepared in Comparative Example 2, the cobalt-doped bamboo powder biochar (Co-BC) prepared in Comparative Example 3, and the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1.
[0016] Figure 4 Cyclic voltammetry (CV) curves of the original bamboo powder biochar (BC) prepared in Comparative Example 1 of the present invention, the boron-doped bamboo powder biochar (B-BC) prepared in Comparative Example 2, the cobalt-doped bamboo powder biochar (Co-BC) prepared in Comparative Example 3, and the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1.
[0017] Figure 5 Electrochemical impedance spectroscopy (EIS) graphs of the original bamboo powder biochar (BC) prepared in Comparative Example 1 of the present invention and the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1.
[0018] Figure 6 These are the adsorption and degradation effect diagrams of the original bamboo powder biochar (BC) prepared in Comparative Example 1 of the present invention, the boron-doped bamboo powder biochar (B-BC) prepared in Comparative Example 2, the cobalt-doped bamboo powder biochar (Co-BC) prepared in Comparative Example 3, and the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1.
[0019] Figure 7 This is a time-degradation efficiency diagram of the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1 of the present invention under different pH conditions.
[0020] Figure 8 This is a diagram showing the degradation effect of the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1 of the present invention on ciprofloxacin (CIP).
[0021] Fig. 9This is a time-degradation efficiency diagram of the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1 of the present invention under different quenching agent conditions.
[0022] Fig.10 This is a diagram showing the degradation effect of the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst prepared in Examples 1, 6 to 9 of the present invention. DETAILED DESCRIPTION
[0023] The present invention is further illustrated by the following examples, but is not limited to the following examples. Example 1
[0024] A method for preparing a boron-cobalt coordinated graphitization calcium-rich carbon-based catalyst of the present invention comprises the following steps: (1) Use waste bamboo powder, wash it with anhydrous ethanol and ultrapure water, dry it to constant weight, and grind it through a 100-mesh sieve.
[0025] (2) Mix bamboo powder, boric acid, cobalt salt and water in a mass ratio of 5:1.5:1:50 and stir at 300 rpm for 6 h using a magnetic stirrer to achieve full impregnation.
[0026] (3) The mixture was filtered, dried, and ground in sequence, placed in a crucible and wrapped with aluminum foil, and then placed in a tubular furnace for pyrolysis at 600°C in a nitrogen atmosphere for 2 h to obtain modified biochar.
[0027] (4) The biochar was washed with ultrapure water until the filtrate was neutral, dried in an oven, ground and sieved to obtain a boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst, denoted as CoB-BC.
[0028] Comparative Example 1: A method for preparing raw bamboo powder biochar comprises the following steps: (1) Use waste bamboo powder, wash it with anhydrous ethanol and ultrapure water, dry it to constant weight, and grind it through a 100-mesh sieve.
[0029] (2) The treated bamboo powder was placed in a crucible and wrapped with aluminum foil, and then placed in a tube furnace for pyrolysis at 600 °C in a nitrogen atmosphere for 2 h to obtain the original bamboo powder biochar, denoted as BC.
[0030] Comparative Example 2: A method for preparing boron-doped bamboo powder biochar comprises the following steps: (1) Use waste bamboo powder, wash it with anhydrous ethanol and ultrapure water, dry it to constant weight, and grind it through a 100-mesh sieve.
[0031] (2) Mix bamboo powder, boric acid and water in a mass ratio of 5:1.5:50 and stir at 300 rpm for 6 h using a magnetic stirrer to achieve full impregnation.
[0032] (3) The mixture was filtered, dried, and ground in sequence, placed in a crucible and wrapped with aluminum foil, and then placed in a tubular furnace for pyrolysis at 600°C in a nitrogen atmosphere for 2 h to obtain modified biochar.
[0033] (4) The biochar was washed with ultrapure water until the filtrate was neutral, dried in an oven, ground and sieved to obtain boron-doped bamboo powder biochar, denoted as B-BC.
[0034] Comparative Example 3: A method for preparing cobalt-doped bamboo powder biochar comprises the following steps: (1) Use waste bamboo powder (BC), wash it with anhydrous ethanol and ultrapure water, dry it to constant weight, and grind it through a 100-mesh sieve.
[0035] (2) Bamboo powder, cobalt nitrate hexahydrate and water were mixed in a mass ratio of 5:1:50 and stirred at 300 rpm for 6 h using a magnetic stirrer to achieve full impregnation.
[0036] (3) The mixture was filtered, dried, and ground in sequence, placed in a crucible and wrapped with aluminum foil, and then placed in a tubular furnace for pyrolysis at 600°C in a nitrogen atmosphere for 2 h to obtain modified biochar.
[0037] (4) The biochar was washed with ultrapure water until the filtrate was neutral, dried in an oven, ground and sieved to obtain cobalt-doped bamboo powder biochar, denoted as Co-BC.
[0038] BET analysis was performed and the BC was found to be 11.82 m 2 / g, CoB-BC is 51.98 m 2 / g.
[0039] Figure 1This is an SEM image of the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1 of the present invention (Figures (a) and (b) have different magnifications). The micromorphology of CoB-BC presents a rich and uniform pore structure, which is attributed to the improvement of the degree of graphitization by B and the regulation of defects by Co. The SEM results are consistent with the BET results. Under the full modification of boric acid and cobalt nitrate, the specific surface area of CoB-BC increases and the number of reaction sites increases, which is beneficial to the adsorption of PMS and antibiotics by CoB-BC. At the same time, adsorption further promotes the contact of various substances and the transfer of electrons, thereby promoting degradation. The uniform pore structure of CoB-BC provides a good carrier for the loading of metal particles, and the encapsulation effect of biochar greatly reduces the leaching of metals.
[0040] Figure 2 XRD patterns of the original bamboo powder biochar (BC) prepared in Comparative Example 1 of the present invention, the boron-doped bamboo powder biochar (B-BC) prepared in Comparative Example 2, the cobalt-doped bamboo powder biochar (Co-BC) prepared in Comparative Example 3, and the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1. Figure 2 It can be clearly observed that BC itself has a high degree of crystallinity. This is because bamboo powder contains rich calcium, the main form of which is CaCO 3 and CaMg(CO 3 ) 2 The doping of B makes CaCO 3 and CaMg(CO 3 ) 2 The peak intensity is reduced because boric acid reacts with it at high temperature. At the same time, the pore structure of the catalyst is optimized, which not only increases the specific surface area but also enhances the adsorption performance of the material. Co doping seriously destroys the CaMg(CO 3 ) 2 morphology, and may also make CaCO 3 When B and Co exist at the same time, B is embedded in the lattice of metal Co, and there is no obvious Co structure, indicating that the content of Co is small. Under the synergistic effect of B and Co, the overall performance is 3 ) 2 BC has a certain graphite carbon structure, B slightly promotes the degree of graphitization, and Co introduces defects, and finally CoB-BC shows a higher degree of graphitization.
[0041] Figure 3The Raman spectra of the original bamboo powder biochar (BC) prepared in Comparative Example 1 of the present invention, the boron-doped bamboo powder biochar (B-BC) prepared in Comparative Example 2, the cobalt-doped bamboo powder biochar (Co-BC) prepared in Comparative Example 3, and the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1. Figure 3 The D band and G band in the Raman spectrum reflect the graphitization degree of different materials. D / I G They are 0.86, 0.83, 0.89, and 0.85, respectively. BC has a high degree of graphitization and is a good metal loading carrier, which can slow down the leakage of metal elements. B has a small atomic radius and can easily enter the carbon lattice when modifying the original bamboo powder. B replaces sp2 and sp3 structures and promotes graphitization. On the contrary, the introduction of Co brings more defects, which is consistent with the results of XRD. B and Co work synergistically to construct a CoB-BC with a high degree of graphitization and rich active sites.
[0042] Figure 4 CV graphs of the original bamboo powder biochar (BC) prepared in Comparative Example 1 of the present invention, the boron-doped bamboo powder biochar (B-BC) prepared in Comparative Example 2, the cobalt-doped bamboo powder biochar (Co-BC) prepared in Comparative Example 3, and the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1. Figure 4 The electron transfer properties of different materials were distinguished. According to the amplitude of current change, the electron conduction rate shows the rule of CoB-BC > Co-BC > B-BC > BC. The main components of BC are carbon, calcium, magnesium, etc., which have low electrical conductivity. After the addition of heteroatom B, the electron conduction performance of B-BC is accelerated due to the promotion of graphitization by B. After the introduction of metal Co and non-metal B, it has stronger electrochemical activity, and the CV curve of CoB-BC shows obvious redox peaks, indicating the existence of reversible redox reactions, which is attributed to the promotion of Co valence cycle by B.
[0043] Figure 5 These are EIS graphs of the original bamboo powder biochar (BC) prepared in Comparative Example 1 of the present invention and the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1. Figure 5 The conductivity of the catalyst can be determined by comparing the EIS graphs of BC and CoB-BC. The smaller the slope of the curve, the smaller the resistivity and the greater the conductivity. As can be seen from the figure, the modification of BC by B and Co accelerates the efficiency of electron transfer. The electron transfer pathway belongs to the non-free radical pathway, which increases the proportion of the non-free radical pathway in the mechanism of pollutant removal. Example 2
[0044] Comparative Examples 1-3 and Example 1 are used in treating electron-rich antibiotic wastewater, with ofloxacin as the target pollutant, comprising the following steps: Weigh 50 mg of the original bamboo powder biochar (BC) prepared in Comparative Example 1, the boron-doped bamboo powder biochar (B-BC) prepared in Comparative Example 2, the cobalt-doped bamboo powder biochar (Co-BC) prepared in Comparative Example 3, and the boron-cobalt coordinated graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1, and add them to 100 mL of 10 mg / L ofloxacin solution, respectively, and place them in a shaker for adsorption reaction; based on the above conditions, add 1.5 mL of 0.1 M peroxymonosulfate (PMS) solution to each conical flask, and place them in a shaker for degradation reaction. Take 7 samples at a sampling interval of 10 minutes, take 3 mL each time, and quench with 100 microliters of sodium thiosulfate. Finally, the concentration of ofloxacin was determined by ultraviolet spectrophotometer.
[0045] Figure 6 The adsorption and degradation effect diagram of the original bamboo powder biochar (BC) prepared in Comparative Example 1 of the present invention, the boron-doped bamboo powder biochar (B-BC) prepared in Comparative Example 2, the cobalt-doped bamboo powder biochar (Co-BC) prepared in Comparative Example 3, and the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1 (C in the figure) t represents the concentration of pollutants after degradation, C 0 Represents the initial concentration of the pollutant). In the figure, the adsorption and degradation effects of BC are very poor. After the introduction of B or Co, the adsorption and degradation rates of the catalyst are improved. Among them, CoB-BC has the best removal effect. Boric acid can react with calcium species in bamboo powder to increase the specific surface area, improve the pore structure, and polarize the carbon surface; Co can introduce defects and increase the active sites of the catalyst, thereby enhancing the adsorption effect. B itself can cut the OO bond of PMS, and can also promote electron transfer and the valence cycle of Co. In addition, Co has high oxidation activity. The ternary synergy of boron, cobalt and calcium promotes CoB-BC to achieve complete removal of ofloxacin within 40 minutes, and the ICP measurement results show that there is no metal ion leaching. Example 3
[0046] The application of boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst in the degradation of electron-rich antibiotic wastewater under different pH conditions, with ofloxacin as the target pollutant, includes the following steps: The control group was set up without pH adjustment. The experimental group used HCl and NaOH to adjust the pH value of 100 mL ofloxacin solution with a concentration of 10 mg / L to 3, 5, 7, 9, and 11 respectively. Then, 50 mg of catalyst and 1.5 mL of 0.1 M PMS solution were added to the conical flask simultaneously and placed in a shaker at 25 ° C for degradation reaction. With a sampling interval of 10 minutes, a total of 7 samples were taken, 3 mL was taken each time, and quenched with 100 microliters of sodium thiosulfate. Finally, the concentration of loxacin was determined by ultraviolet spectrophotometer.
[0047] Figure 7 The figure is a time-degradation efficiency diagram of the boron-cobalt coordinated graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1 of the present invention under different pH conditions. When the pH is 3-9, the degradation curve almost overlaps with the control group curve, indicating that the pH range does not affect the degradation efficiency of the catalyst, and the catalyst has a wide pH application range and stability. When the pH is 11, the degradation efficiency of ofloxacin in a strong alkaline environment decreases slightly, which is because the pH affects the generation of ROS and the surface charge of the catalyst, but the removal rate can still reach 90%. Example 4
[0048] Example 1 is applied in treating electron-rich antibiotic wastewater, with ciprofloxacin (CIP) as the target pollutant, comprising the following steps: Weigh 50 mg of the boron-cobalt coordinated graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1, add them to 100 mL of 10 mg / L ciprofloxacin solution, add 1.5 mL of 0.1 M permonosulfate (PMS) solution in a conical flask, and place it in a shaker for degradation reaction. Take 7 samples at a sampling interval of 10 minutes, take 3 mL each time, and quench with 100 microliters of sodium thiosulfate. Finally, the concentration of ciprofloxacin is determined by ultraviolet spectrophotometer.
[0049] Figure 8 The figure is a diagram of the degradation effect of ciprofloxacin (CIP) on boron cobalt-cobalt-graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1 of the present invention. Similar to the degradation effect of ofloxacin, ciprofloxacin achieved 100% degradation in 30 minutes. This is because ciprofloxacin and ofloxacin belong to the same quinolone antibiotics, with similar structures and degradation pathways, and both belong to electron-rich antibiotics. Under the adsorption and catalytic action of CoB-BC, PMS forms a complex with antibiotics, and CoB-BC acts as a bridge for electron transfer. The electron-rich antibiotics lose electrons and are gradually oxidized. At the same time, under the attack of ROS, CoB-BC achieves efficient degradation of antibiotics. Example 5
[0050] The application of boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst to degrade electron-rich antibiotic wastewater under different quenching conditions, with ofloxacin as the target pollutant, includes the following steps: Weigh 50 mg of the boron-cobalt coordinated graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1, add them to 100 mL of 10 mg / L ofloxacin solution, add 1.5 mL of 0.1 M permonosulfate (PMS) solution in a conical flask, and add different concentrations and types of quenchers to different conical flasks, and place them in a shaker for degradation reaction. Take 7 samples at a sampling interval of 10 minutes, take 3 mL each time, and quench with 100 microliters of sodium thiosulfate. Finally, the concentration of ofloxacin is determined by ultraviolet spectrophotometer.
[0051] Fig. 9 This is a time-degradation efficiency diagram of the boron-cobalt coordinated graphitized calcium-rich carbon-based catalyst (CoB-BC) prepared in Example 1 of the present invention under different quenching agent conditions. Methanol (MeOH) is used to quench sulfate radicals (SO 4 ·- ) and hydroxyl radicals (·OH), tert-butyl alcohol (TBA) can quench ·OH, L-histidine and furfuryl alcohol (FFA) target singlet oxygen ( 1 O 2 ), p-benzoquinone (PBQ) can quench superoxide radicals (O 2 ·- ). When the concentrations of MeOH and TBA were 10mM and 50mM, the inhibitory effect on the reaction system was small, indicating that SO 4 ·- and ·OH are not the main ROS; when the concentrations of L-histidine and FFA are 5mM and 10mM, the degradation rate of ofloxacin is almost 0, and the reaction process is completely inhibited, which indicates that 1 O 2 It plays a major role in the degradation process, which indicates that the non-radical pathway is the main degradation pathway of the reaction system, which is consistent with the wide pH range of 3-11 that CoB-BC is suitable for. The slight inhibition of PBQ on degradation indicates that there is O in the reaction process. 2 ·- , and studies have shown that O 2 ·- Can be converted into 1 O 2 , more prominent 1 O 2 The importance of. Example 6
[0052] A method for preparing a boron-cobalt coordinated graphitization calcium-rich carbon-based catalyst of the present invention comprises the following steps: (1) Use waste bamboo powder, wash it with anhydrous ethanol and ultrapure water, dry it to constant weight, and grind it through a 100-mesh sieve.
[0053] (2) Mix bamboo powder, boric acid, cobalt salt and water in a mass ratio of 5:0.5:1:50 and stir at 300 rpm for 6 h using a magnetic stirrer to achieve full impregnation.
[0054] (3) The mixture was filtered, dried, and ground in sequence, placed in a crucible and wrapped with aluminum foil, and then placed in a tubular furnace for pyrolysis at 600°C in a nitrogen atmosphere for 2 h to obtain modified biochar.
[0055] (4) The biochar was washed with ultrapure water until the filtrate was neutral, dried in an oven, ground and sieved to obtain a boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst, denoted as CoB 0.5 -BC. Example 7
[0056] A method for preparing a boron-cobalt coordinated graphitization calcium-rich carbon-based catalyst of the present invention comprises the following steps: (1) Use waste bamboo powder, wash it with anhydrous ethanol and ultrapure water, dry it to constant weight, and grind it through a 100-mesh sieve.
[0057] (2) Mix bamboo powder, boric acid, cobalt salt and water in a mass ratio of 5:1:1:50 and stir at 300 rpm for 6 h using a magnetic stirrer to achieve full impregnation.
[0058] (3) The mixture was filtered, dried, and ground in sequence, placed in a crucible and wrapped with aluminum foil, and then placed in a tubular furnace for pyrolysis at 600°C in a nitrogen atmosphere for 2 h to obtain modified biochar.
[0059] (4) The biochar was washed with ultrapure water until the filtrate was neutral, dried in an oven, ground and sieved to obtain a boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst, denoted as CoB 1 -BC. Example 8
[0060] A method for preparing a boron-cobalt coordinated graphitization calcium-rich carbon-based catalyst of the present invention comprises the following steps: (1) Use waste bamboo powder, wash it with anhydrous ethanol and ultrapure water, dry it to constant weight, and grind it through a 100-mesh sieve.
[0061] (2) Bamboo powder, boric acid, cobalt salt and water were mixed in a mass ratio of 5:1.5:0.1:50 and stirred at 300 rpm for 6 h using a magnetic stirrer to achieve full impregnation.
[0062] (3) The mixture was filtered, dried, and ground in sequence, placed in a crucible and wrapped with aluminum foil, and then placed in a tubular furnace for pyrolysis at 600°C in a nitrogen atmosphere for 2 h to obtain modified biochar.
[0063] (4) The biochar was washed with ultrapure water until the filtrate was neutral, dried in an oven, ground and sieved to obtain a boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst, denoted as Co 0.1 B-BC. Example 9
[0064] A method for preparing a boron-cobalt coordinated graphitization calcium-rich carbon-based catalyst of the present invention comprises the following steps: (1) Use waste bamboo powder, wash it with anhydrous ethanol and ultrapure water, dry it to constant weight, and grind it through a 100-mesh sieve.
[0065] (2) Mix bamboo powder, boric acid, cobalt salt and water in a mass ratio of 5:1.5:0.5:50 and stir at 300 rpm for 6 h using a magnetic stirrer to achieve full impregnation.
[0066] (3) The mixture was filtered, dried, and ground in sequence, placed in a crucible and wrapped with aluminum foil, and then placed in a tubular furnace for pyrolysis at 600°C in a nitrogen atmosphere for 2 h to obtain modified biochar.
[0067] (4) The biochar was washed with ultrapure water until the filtrate was neutral, dried in an oven, ground and sieved to obtain a boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst, denoted as Co 0.5 B-BC.
[0068] Fig.10 The degradation effect diagram of the boron-cobalt coordinated graphitized calcium-rich carbon-based catalyst prepared in Examples 1 and 6-9 of the present invention is shown in the figure. It can be seen from the figure that within a given range, the overall performance of the catalysts prepared with different mass ratios tends to be consistent, and ofloxacin is rapidly degraded, with a degradation rate of nearly 90% at 10 minutes, and the degradation rate gradually stabilizes after 30 minutes. Fig.10 This shows that within a certain mass ratio range, highly efficient catalysts can be successfully prepared. In addition, the degradation performances of catalysts prepared at different ratios are still different, among which the CoB-BC prepared in Example 1 has the best degradation effect.
Claims
1. A method for preparing a boron-cobalt coordinated graphitization calcium-rich carbon-based catalyst, characterized in that The following steps are involved: (1) mixing bamboo powder, boric acid, cobalt salt and water in a mass ratio of 5:0.5-1.5:0.1-1:50-100, and using a magnetic stirrer to achieve full impregnation; (2) placing the modified biomass obtained in step (1) into a tubular furnace, pyrolyzing it at 400-600° C. in a nitrogen atmosphere, washing, drying, and grinding to obtain a boron-cobalt doped boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst.
2. The method for preparing the boron-cobalt coordinated graphitization calcium-rich carbon-based catalyst according to claim 1, characterized in that: In step (1), the cobalt salt is cobalt nitrate hexahydrate.
3. The method for preparing the boron-cobalt coordinated graphitization calcium-rich carbon-based catalyst according to claim 1, characterized in that: In step (1), the magnetic stirring speed is 200 to 400 rpm and the immersion time is 5 to 7 hours.
4. The method for preparing the boron-cobalt coordinated graphitization calcium-rich carbon-based catalyst according to claim 1, characterized in that: The pyrolysis time in step (2) is 1 to 3 hours.
5. A boron-cobalt synergistic graphitization calcium-rich carbon-based catalyst prepared by the preparation method according to any one of claims 1 to 4.
6. Use of the boron-cobalt synergistic graphitized calcium-rich carbon-based catalyst according to claim 5 in treating antibiotic wastewater.
7. The use according to claim 6, characterized in that: Catalysts and PMS are added simultaneously to antibiotic wastewater to achieve efficient removal of antibiotics.
8. The use according to claim 6, characterized in that: The catalyst achieved 100% degradation of quinolone antibiotics within 30 minutes.
Citation Information
Patent Citations
Activated carbon supported cobalt oxide catalyst and application of same in organic pollutant degradation
CN102580746A
Preparation method of biochar-supported cobaltosic oxide catalytic material
CN111013590A
3D catalyst for catalytic degradation of organic pollutants as well as preparation and application of 3D catalyst
CN111408373A
Method for preparing boron-doped porous carbon material with high specific surface area from biomass
CN111994907A
Cobalt-boron co-doped carbon nitride catalyst and preparation method thereof
CN116212930A